Effects of composition and phase relations on mechanical properties and crystallization of silicate glasses. Issue 8 (10th April 2021) - Kilinc, Erhan; Bell, Anthony M. T.; Bingham, Paul A.; Hand, Russell J.
Abstract: Crystallization, mechanical properties, and workability are all important for the commercialization and optimization of silicate glass compositions. However, the inter‐relations of these properties as a function of glass composition have received little investigation. Soda‐lime‐silica glasses with Na2 O‐MgO‐CaO‐Al2 O3 ‐SiO2 compositions relevant to commercial glass manufacture were experimentally studied and multiple liquidus temperature and viscosity models were used to complement the experimental results. Liquidus temperatures of the fabricated glasses were measured by the temperature gradient technique, and Rietveld refinements were applied to X‐Ray powder diffraction (XRD) data for devitrified glasses, enabling quantitative determination of the crystalline and amorphous fractions and the nature of the crystals. Structural properties were investigated by Raman spectroscopy. Acoustic echography, micro‐Vicker's indentation, and single‐edge‐notched bend testing methods were used to measure Young's moduli, hardness, and fracture toughness, respectively. It is shown that it is possible to design lower‐melting soda‐lime‐silica glass compositions without compromising their mechanical and crystallization properties. Unlike Young's modulus, brittleness is highly responsive to the composition in soda‐lime‐silica glasses, and notably low brittleness values can be obtained in glasses with compositions in the wollastonite primary phase field: an effect that is more pronounced in the silica primary phase field. The measured bulk crystal fractions of the glasses subjected to devitrification at the lowest possible industrial conditioning temperatures indicate that soda‐lime‐silica glass melts can be conditioned close to their liquidus temperatures within the compositional ranges of the primary phase fields of cristobalite, wollastonite, or their combinations.